Production of AgNPs in unprocessed leaf extract and their identification by UV-Vis spectroscopy, Diffraction, and transmission electron microscopy: Exploring the Potential of Plant-based Synthesis of AgNPs and Their Role in Combatting Antibiotic Resistance (Journal of Advances and Scholarly Researches in Allied Education, 2022)
There is a low-cost and environmentally friendly alternative to conventional nanoparticlesynthesis that can be obtained from plant extracts. The present paper reports the reduction of silver ionswith extracts from Emblica officinalis, and Eucalyptus hybrida, resulting in stable, homogeneous silvernanoparticles. Silver nanoparticles can be obtained by this straightforward method in a short amount oftime, making it of interest to scientists around the world. Various techniques, including UV-Visspectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), and energy diffraction Xray(EDX) analysis, were used to determine that the silver nanoparticles range in size from 20 nm to 80nm and have a variety of shapes and sizes. Using X-ray diffraction, researchers found that thenanostructures had a crystal structure characteristic of a face-centered cubic. The presence of anabsorption peak in UVVis spectra is evidence that they are manufactured. The development of a safeand environmentally benign method for the biological synthesis of metallic nanoparticles is a major stepforward in the realm of nanobiotechnology's practical applications. Because of their biogenic nature,silver nanoparticles (Ag-NPs) may show to be a more effective medication option. Antibiotic resistancehas spread at a frightening rate due to careless usage of the drugs. Ag-NPs have the potential to providea one-size-fits-all answer to this pressing issue.